Live and Let Die…: Necropolitics and Zombie Film Tropes During the COVID-19 Pandemic1. Issue 1 (1st April 2022) - Filho, Lúcio Reis
Abstract : Many horror film tropes converged with the COVID-19 global health emergency. News media coverage of the pandemic has daily evoked several tropes of one horror film subgenre in particular—zombie films—such as unexplainable disease, lab-leak conspiracies, the silence or denial of authorities, political disarticulation, the buzz of the media, increasing mortality rates, the collapse of healthcare systems, and urban landscapes as eerily empty spaces. Arguably, the undead character at the heart of zombie films provides a critique of late capitalism, and of the social issues that we have seen highlighted by the COVID-19 pandemic, such as the stigma of the infected, the deepening of social inequalities, and the challenges of quarantine and the segregation inherent to it. In this paper, we intend to analyze the zombie film subgenre in the light of three leading concepts: Mary Douglas's archetype of dirt, Byung-Chul Han's immunological paradigm, and Achille Mbembe's notion of necropolitics, the latter being related to the ultimate expression of sovereignty—the power and the ability to decide who lives and who may die.